A Bayesian approach to reliability of MSE walls. Issue 1 (2nd January 2021) - Bozorgzadeh, Nezam; Bathurst, Richard J.
ABSTRACT: A shortcoming of the typical use of the frequentist probabilistic approach in reliability analysis of limit state equations that appear in the geotechnical literature is that estimates of the uncertainty in reliability index (probability of failure) are not made. A Bayesian approach is demonstrated in the paper to overcome this shortcoming using the example of the pullout limit state for internal stability of mechanically stabilised earth (MSE) walls. The paper shows that in the Bayesian context, reliability index or probability of failure are modelled as probability distributions, and therefore readily incorporate the uncertainty in their estimates. The general approach provides a tool to communicate the level of risk to stakeholders that follows from the choice of design method and guidance to reduce uncertainty on the estimate of reliability. For practical purposes, the predictive reliability index may be used as an alternative measure of margin of safety that takes this uncertainty into account.